2018
DOI: 10.1590/0104-07072018003720017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Eficiência Da Limpeza E Desinfecção De Superfícies Em Uma Unidade Básica De Saúde

Abstract: RESUMO Objetivo: avaliar o efeito de intervenções educativasna limpeza e desinfecção de superfícies em uma unidade básica de saúde. Métodos: trata-se de um estudo prospectivo, analítico com abordagem quantitativa. O estudo foi realizado em uma unidade básica de saúde, onde atuam duas equipes da Estratégia de Saúde da Família. Optou-se por avaliar a limpeza e desinfecção das superfícies: carrinho de curativo, balcão da recepção, mesa ginecológica, maca do paciente e mesa de consulta de enfermagem, utilizando-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Alternatively, a study carried out in a primary healthcare unit observed a decrease in microbial charge through ACC and ATP bioluminescence on five surfaces by comparing outcomes obtained before and after the implementation of a cleaning and disinfection program. This effect persisted for two months, when a new assessment was performed using the same techniques [7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, a study carried out in a primary healthcare unit observed a decrease in microbial charge through ACC and ATP bioluminescence on five surfaces by comparing outcomes obtained before and after the implementation of a cleaning and disinfection program. This effect persisted for two months, when a new assessment was performed using the same techniques [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects may be related to negative impacts of interventions and help explain these results. The main ones are nonadherence to the protocol; inadequacy of the executed procedures; use of contaminated materials, utensils or equipment; and lack of feedback to the team [7, 16]. The latter has been pointed out as a decisive element to achieve positive results, given that it tends to encourage the team, allowing the team to raise awareness of its role in behavior change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations